Injuries and deaths due to tree failure in The Netherlands: analysis of observational data from 1998-2021 - van Haaften, Marinus; Gardebroek, Cornelis; Heijman, Wim; Meuwissen, Miranda P M (Scientific reports, 2024)
Urban and roadside trees contribute to health and resilience. However, when trees or branches fall, it can cause injuries or deaths. This study examined trends and variations of injuries and deaths due to tree failure in The Netherlands from 1998 to 2021, considering urban-rural location, sex, age and traffic mode. This study is the first to describe long-term trends in injuries and deaths due to tree failure from 1998-2021. The standardised rate of injuries per 1,000,000 population increased from 0.14 (SE 0.10) in 1998 to 0.91 (SE 0.21) in 2021, with an annual percentage increase of 5.3% (p = 0.002). The data shows a strong increase for rural areas, contrary to urban ones. The annual percentage increase in rural areas was 13.2% (p < 0.001) while injuries in urban areas increased with 3.0% (p = 0.026), which revealed large urban-rural disparities. A trend was absent in the frequency of deaths. More attention needs to be given to investigating causes, drivers and stressors associated with tree failure-related injuries. In particular, efforts should be made to reduce the prevalence in rural areas. The increase in injuries over time makes it necessary to create awareness and share knowledge among residents and local governments about tree failure risks.
Keywords: dospělí; Female; Infant; Netherlands; dítě; předškolní dítě; Urban Population; Mortality; Adult; Injuries; mladý dospělý; ženské pohlaví; Accidents, Traffic; Adolescent; Public health risk; lidé; Wounds and Injuries; Aged, 80 and over; stromy; Nizozemsko; venkovské obyvatelstvo; Male; Tree risk management; Urban trees; kojenec; Aged; Young Adult; městské obyvatelstvo; Child, Preschool; Tree failure; lidé středního věku; rány a poranění; senioři nad 80 let; Child; senioři; mužské pohlaví; Trees; Middle Aged; mladiství; Rural Population; dopravní nehody; Humans